Critical and supercritical properties of Lennard–Jones fluids - Heyes, David M. (2021)
Critical properties for Lennard-Jones fluids are seen to be consistent with an alternative description of liquid-gas criticality to the van der Waals hypothesis. At the critical temperature (T-c) there is a critical dividing line on the Gibbs density surface rather than a critical point singularity. We report high-precision thermodynamic pressures from MD simulations for more than 2000 state points along 7 near-critical isotherms, for system sizes N=4096 and 10,976 for a Lennard-Jones fluid. We obtain k(B)T(c)/epsilon = 1.3365 +/- 0.0005 and critical pressure p(c)sigma(3)/epsilon = 0.1405 +/- 0.0002 which remains constant between two coexisting densities rho(c)(gas) sigma(3) = 0.266 +/- 0.01 and rho(c)(liquid) sigma(3) = 0.376 +/- 0.01 determined by supercritical percolation transition loci. A revised plot of the liquid-vapor surface tension shows that it goes to zero at this density difference, which, along with a direct evaluation of Gibbs chemical potential along the critical isotherm, reaffirms a coexisting dividing line of critical states. Analysis of the distribution of clusters from MD simulations along a supercritical isotherm (T*=1.5) gives new insight into the supercritical boundaries of gas and liquid phases, and the nature of the supercritical mesophase. (C) 2013 Elsevier B.V. All rights reserved.